Testing for the money: an analysis on the interdependence of participation in international large-scale assessments and development aid networks - Besche-Truthe, Fabian; Seitzer, Helen (Frontiers in Education, 2025)
IntroductionInternational Large-Scale Assessments (ILSAs) are widely utilized to benchmark to evaluate the quality of education systems globally. Since 2000, the number of participating countries in these assessments has increased dramatically, revealing the dominance of a few education systems while exposing the deficiencies of many others. Especially for the latter group the question, as to why they participate in ILSAs, is puzzling. Existing literature attributes this participation to domestic factors or the influence of International Organizations. However, we argue that the global spread of ILSAs can also be explained by direct country-to-country dependencies through development aid.MethodsThis study takes an interdependency-inspired approach, focusing on how bilateral development aid networks influence ILSA participation. Using advanced network diffusion and hurdle models, we analyse data from a global set of countries over the period from 1990 to 2012. The models examine the role of development aid distribution in shaping ILSA participation, with particular attention to how participation in ILSAs affects the likelihood of attracting additional donors and aid.ResultsOur analysis reveals that the distribution of development aid has a significant impact on countries’ decisions to participate in ILSAs. Furthermore, we find that countries already involved in ILSAs are more likely to attract additional donors and aid within established donor-recipient dyads. These results demonstrate a clear connection between development aid distribution and the global spread of ILSAs.DiscussionThis study highlights the role of monetary incentives, facilitated by the distribution of development aid, in promoting participation in ILSAs. Our findings suggest that the rapid spread of ILSAs is not solely driven by domestic factors or international organizations but also by the interdependent relationships formed through aid distribution networks. These insights contribute to a broader understanding of the factors driving global educational assessments and provide implications for policy-making in education and development aid.